2022
DOI: 10.1563/aaid-joi-d-21-00310
|View full text |Cite
|
Sign up to set email alerts
|

Bone Graft Osseous Changes After Maxillary Sinus Floor Augmentation: A Systematic Review

Abstract: This systematic review aimed to evaluate computed tomographic scans for volumetric bone gain following lateral sinus floor augmentation of the atrophic posterior maxilla after the use of various bone-grafting materials using. The databases MEDLINE, EMBASE, CINAHL, Cochrane Central Registry of Controlled Trials (CENTRAL), and SCOPUS were used for a comprehensive search for all potentially eligible randomized controlled trials (RCTs), without language restrictions, from the beginning of each database until June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a recent systematic review, Stumbras et al [ 59 ] identified autologous bone as the best-performing graft for inducing new bone formation after MSA. In fact, autologous bone is still considered the gold standard in bone regeneration due to its high capacity for osteoconduction, osteoinduction, and osteogenesis [ 60 ]. However, there remain concerns about patients’ discomfort and potential complications at donor sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review, Stumbras et al [ 59 ] identified autologous bone as the best-performing graft for inducing new bone formation after MSA. In fact, autologous bone is still considered the gold standard in bone regeneration due to its high capacity for osteoconduction, osteoinduction, and osteogenesis [ 60 ]. However, there remain concerns about patients’ discomfort and potential complications at donor sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remain concerns about patients’ discomfort and potential complications at donor sites. Autologous bone has also shown high resorption and less volume gain [ 60 ]. Other bone-grafting materials that offer higher stability have been used, such as anorganic bovine bone.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome of the study was histological assessment. The presence of newly‐formed bone is of utmost importance for successful dental implants, as it enables the implant to integrate securely and anchor within the jawbone 13 . During the dental implant surgery, a 2 mm trephine drill was used to obtain a biopsy from the buccal one‐third of the crest of the alveolar ridge, following the long axis of the ridge.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of newly-formed bone is of utmost importance for successful dental implants, as it enables the implant to integrate securely and anchor within the jawbone. 13 During the dental implant surgery, a 2 mm trephine drill was used to obtain a biopsy from the buccal onethird of the crest of the alveolar ridge, following the long axis of the ridge. This biopsy procedure was performed in 24 participants, with 13 in the control group and 11 in the test group, at the 6-month mark after bone augmentation.…”
Section: Secondary Outcomementioning
confidence: 99%
“…Various materials have been advocated and utilized falling into the categories of allograft, xenograft and synthetic materials. Each category has been well documented for the utilization in sinus augmentation procedures in the literature [ 1 , 2 , 3 ]. Several factors weigh in decisions when selecting a type of osseous graft material.…”
Section: Introductionmentioning
confidence: 99%